Measurement by a cylinder test stand and tyre rolling resistance - Rievaj, Vladimir; Faith, Peter; Dávid, Andrej (Transport, 2006)
Sometimes it is necessary to test how repair affects the properties of the car. These tests are carried out using a cylinder test stand. During the test the tyre is rolling between two cylinders of a small diameter. The question arises whether the rolling resistance of the tyre is the same as the rolling resistance when the wheel is rolling on the plane. If it is not the same what is the reliation between tyre resistances in these two cases? It is an important answer because the change of rolling resistance can affect consumption, the highest speed, engine power and other results of measurement. The paper gives the answer to these questions and describes the method of getting this information.First Published Online: 27 Oct 2010